The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2014
DOI: 10.1038/ncomms5492
|View full text |Cite
|
Sign up to set email alerts
|

Observation of a quantum Cheshire Cat in a matter-wave interferometer experiment

Abstract: From its very beginning, quantum theory has been revealing extraordinary and counter-intuitive phenomena, such as wave-particle duality, Schrödinger cats and quantum non-locality. Another paradoxical phenomenon found within the framework of quantum mechanics is the ‘quantum Cheshire Cat’: if a quantum system is subject to a certain pre- and postselection, it can behave as if a particle and its property are spatially separated. It has been suggested to employ weak measurements in order to explore the Cheshire C… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
234
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 177 publications
(246 citation statements)
references
References 39 publications
(79 reference statements)
11
234
0
Order By: Relevance
“…Aside from possible practical applications (see [3] and references therein), it has been suggested that such values have foundational significance. For example, both their theoretical prediction and experimental observation are said to shed light on "quantum paradoxes" [4][5][6][7][8][9] and even the nature of time [10].…”
mentioning
confidence: 99%
“…Aside from possible practical applications (see [3] and references therein), it has been suggested that such values have foundational significance. For example, both their theoretical prediction and experimental observation are said to shed light on "quantum paradoxes" [4][5][6][7][8][9] and even the nature of time [10].…”
mentioning
confidence: 99%
“…This behavior can be quantified by calculating the weak values using the recorded intensities. Details of this calculation are presented in detail in the Methods of [66]. The final results for the weak values of the populations and magnetic moment are summarized in Table 1.…”
Section: Methodsmentioning
confidence: 99%
“…When researchers separated a beam of neutrons from their magnetic moment (Denkmayr et al 2014;Morgan 2014), they found "the Cat in one place, and its grin in another" (Aharonov et al 2013: 1).…”
Section: Ii) Characters From Carroll's Books On Alice Transmitted Intmentioning
confidence: 99%